Antiepileptics and Cancer Risks - Thapalia, Ravi (Nepal Journal of Neuroscience, 2005)
Happy New Year 2005! Our apology for not being punctual continues, but our promise to be on time in the future remains true. It feels so great to be both growing and developing; now from this issue, we are no more an infant. We’re growing into a toddler. Please help us to take further steps! Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page 90-91